2017
DOI: 10.1007/s00338-017-1638-x
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic and biological trends on coral reefs off Maui, Hawaii

Abstract: 13Coral reefs are characterized by high biodiversity and evidence suggests that reef soundscapes 14 reflect local species assemblages. To investigate how sounds produced on a given reef relate to 15 abiotic and biotic parameters and how that relationship may change over time, an observational 16 study was conducted between September 2014 and January 2016 at seven Hawaiian reefs that 17 varied in coral cover, rugosity, and fish assemblages. The reefs were equipped with temperature 18 loggers and acoustic record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 29 publications
8
37
1
Order By: Relevance
“…Notably, snapping shrimp patterns (1.5–24 kHz) were not associated with either metric. A 16-month follow-up study at additional Pacific Ocean sites showed similar patterns [ 7 ]. Desiderà et al [ 107 ] found a relationship between sound types (not indices) and taxonomic diversity.…”
Section: Initial Methods and Challenges In Assessing Aquatic Acousticmentioning
confidence: 84%
See 2 more Smart Citations
“…Notably, snapping shrimp patterns (1.5–24 kHz) were not associated with either metric. A 16-month follow-up study at additional Pacific Ocean sites showed similar patterns [ 7 ]. Desiderà et al [ 107 ] found a relationship between sound types (not indices) and taxonomic diversity.…”
Section: Initial Methods and Challenges In Assessing Aquatic Acousticmentioning
confidence: 84%
“…Calling patterns vary from daily to seasonally, and have substantial spatial variability [ 101 , 102 ]. In some low-latitude sites, fish and invertebrate sounds that are easily detectable in the summer are overwhelmed and masked by the persistent song of humpback whales in the winter [ 7 ].…”
Section: Initial Methods and Challenges In Assessing Aquatic Acousticmentioning
confidence: 99%
See 1 more Smart Citation
“…Acoustic and visual indicators of reef health can be linked across spatial and temporal scales. Sound-pressure level (particularly at frequencies below 2 kHz) can positively correlate with coral cover, invertebrate abundance, and fish diversity (Kennedy et al, 2010;Kaplan et al, 2015Kaplan et al, , 2018Nedelec et al, 2015;Freeman and Freeman, 2016). Several other acoustic indices such as rates of invertebrate snapping sounds (Butler et al, 2017) and the acoustic complexity index (Pieretti et al, 2011) may also correlate with visual measures of diversity (Nedelec et al, 2015;Bertucci et al, 2016), although the generality of these trends is not fully established (Staaterman et al, 2017).…”
Section: Acoustic Techniquesmentioning
confidence: 99%
“…Future challenges for acoustic monitoring include collating global soundscape databases, identifying, and standardizing the most useful analysis techniques, and improving accessibility for practitioners and managers. Sharing and compiling libraries of recordings will increase the resolution of acoustic monitoring programmes, facilitating more meaningful analyses that account for spatial and temporal variation in reef soundscapes (Kaplan et al, 2018). Engaging local stakeholders, ecosystem managers, and citizen science with coordinated and standardized protocols could also greatly increase the scope of surveying efforts.…”
Section: Acoustic Techniquesmentioning
confidence: 99%